Protogynous functional hermaphroditism in the North American annual killifish, Millerichthys robustus - Domínguez-Castanedo, Omar; Valdez-Carbajal, Sharon; Muñoz-Campos, Tessy M; Huber, Jean H; Reichard, Martin (Scientific reports, 2022)
Sex change (sequential hermaphroditism) has evolved repeatedly in teleost fishes when demographic conditions mediate fundamentally different sex-specific returns for individuals of particular age and size. We investigated the conditions for potential sex change in an annual killifish (Millerichthys robustus) from temporary pools in Mexico. In natural populations, we detected adults with intersex colouration and gonads. Therefore, we experimentally tested whether this apparent sex change can be generated by manipulation of ecological and social conditions, rather than being caused by environmental disturbance. We demonstrated functional protogynous (female-to-male) sex change in 60% replicates, when groups of five females interacted and had a visual and olfactory cue of a male. Only one female changed sex in any given replicate. The sex change never occurred in isolated females. Protandrous (male-to-female) hermaphroditism was not recorded. We characterized gradual changes in behaviour, colouration and gonad structure during the sex change process. The first behavioural signs of sex change were observed after 23 days. Secondary males spawned successfully after 75 days. We discuss the adaptive potential of sex change in short-lived annual fishes through the seasonal decline of males, and during colonization of new habitats. This is the first observation of functional hermaphroditism in an annual killifish.
Keywords: poruchy sexuálního vývoje; Cyprinodontiformes; Disorders of Sex Development; Fundulidae; zvířata; ženské pohlaví; Sex Determination Processes; Female; mužské pohlaví; North America; Male; Animals; procesy určující pohlaví; Severní Amerika